BATIK SEBAGAI GAYA HIDUP MASYARAKAT YOGYAKARTA DAN SURAKARTA - Sri Marwati (Institut Seni Indonesia Surakarta, 2011)
Lifestyle is one of the popular term in global and modern world. Their appearance does not necessarily exist, but is supported by the habitus and image of that shaped it. Any individual or group has always wanted to show his identity through their chosen lifestyle. One of them is by using a particular clothing. Since the first in the Java culture, batik is used by the kingdom as a marker of status, and are realized or not the kingdom was applied a certain lifestyle. As age advances, now lifestyle wear clothing with a particular motif widely followed by the community. There are some ideological contradictions associated with the development of lifestyle by using the batik in Indonesia. On the one side, batik as a lifestyle is the result of capitalist production which have a conflict within it, and the other side, batik as a lifestyle is a form of creativity necessary for social and cultural progress.